Perilaku Keluarga dalam Pencegahan Penyakit Demam Berdarah Dengue (DBD) di Kelurahan Kadipiro Kecamatan Banjarsari Kota Surakarta - Rizky Nur Andriyansah; Tri Susilowati (STIKes Patria Husada Blitar, 2016)
Dengue is one of the most infectious diseases in the world. It is estimated one hundred million people are infected with dengue fever every year year. Kadipiro is one of endemic areas of dengue fever and always the case is always increasing in every year. In 2012, there were 7 cases of dengue hemorrhagic fever and increased to 48 cases in 2013. The Purpose of this study was to determine the behavior determinants of the family in the prevention of dengue hemorrhagic fever in the Kadipiro village, Banjarsari district Surakarta city. The research design was descriptive, with 99 respondents used cluster random sampling and univariate analysis techniques. The result; the behavior determinant of the family in the prevention of dengue fever based on knowledge: 76 respondents have a good knowledge and 23 respondents had a poor knowledge. Perception : 69 respondents have a good perception and 30 respondents had a poor perception. Motivation: 65 respondents have a good motivation and 34 respondents had a poor motivation, Cross-tabulation of knowledge and perception: respondents who had a good knowledge and a good perception was 59 respondents, and poor knowledge and perception of good was10 respondents. Cross-tabulation of knowledge and motivation: respondents who had a good knowledge and a good motivation were 57 respondents, and poor knowledge and motivation of good were 8 respondents. The Determinants of family behavior in the prevention of dengue hemorrhagic fever (DHF ) was based on the knowledge which was mostly good. The perceptions and motivations were mostly good. Cross-tabulation of knowledge and perception was good. Cross-tabulation of knowledge and motivation was good.